The Hidden Cost of Labor Market Entry During Recession: Unemployment Rate at Entry and Occupational Injury Risk of Young Workers - Roberto Leombruni; Tiziano Razzolini; Francesco Serti (Institute for the Study of Labor (IZA), 2015)
A unique dataset from Italy is used to study the effect of unfavorable business cycle conditions at entry on future workplace safety of young workers. We find that higher local unemployment rates at entry have a positive effect both on severe injuries and non-severe injuries. While the impact of unemployment at entry on severe injuries is constant over time, the effect on non-severe injuries is less pronounced and increases with experience, thus indicating that the reporting behavior is affected by initial conditions. In addition, the same cohorts of workers experience slower wage growth, despite being initially compensated for the occupational injury risk. These results suggest that entrants during recession may be persistently locked into low quality jobs and that the mix of hazardous tasks offered by employers throughout the business cycle can be used to overcome wage and other institutional rigidities of the Italian labor market.
Keywords: J24; J28; J31; 330; unemployment at entry; young workers; workplace injury; job amenities